If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3(3x) = 68 Remove parenthesis around (3x) 8x + 3 * 3x = 68 Multiply 3 * 3 8x + 9x = 68 Combine like terms: 8x + 9x = 17x 17x = 68 Solving 17x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '17'. x = 4 Simplifying x = 4
| -9z+12=10z+12+4z | | 12(14z-11)= | | (2x+4)+(2x+2)=4(x-1)+8 | | Y-1=-x-3 | | =3x+7 | | -5-2x=-(-x-1) | | -2x+6-2x=-4x+6 | | 4t+3t-t+17=8+-3 | | x^2+4x+4=121 | | 7t(t-16)=0 | | 4+13g=17+4g+10g | | (8n+8)-(9n+3)= | | (3-w)(2w-1)=0 | | (n+7)-(6n+(-2))= | | a+238=-5a+4 | | 4x-(6+7)=7x-23 | | xy=a-b | | 5.8(3+3x)-3.4=14 | | (-10.3)+(-0.08)x=-4.7 | | (2n+2)-(-3n+3)= | | (1-3x)-(8-10x)= | | 19+2g=-17g-15+2g | | 4+a=15 | | 3000-20%= | | (-3n+(-6))-(-5n+2)= | | 5(3)=10y+20 | | 16(-10-19y)+15y= | | 8-4+8= | | 2(+4)+6=22 | | 31x+115=84 | | -4x-44+x=31 | | 8(x-8)-2(x-1)+5x= |